Computer Troubleshooting Expert System Damage Certainty Factor Method Using Web Based - Fitri Mijaswari; Sulindawaty Sulindawaty (Information Technology and Science (ITScience), 2020)
The problems are most common in essence PT.Sinar Blessings Prosperity is still much work to be done manually, as is the case particularly in the logistics department of administration calculations using a single computer, use the computer that is still its own random origin are still common will of computer technology , where if there is damage to require a long time to fix his computer. Therefore, in this study using expert system troubleshooting computer malfunction with the methods certanty factor to help PT. Sinar Inti Sejahtera Blessing in detecting damage to the computer, so as to minimize the company's performance, minimize expenditures on computer repair, thus better able to improve the performance of employees in PT.Sinar Inti Sejahtera Blessing.